2022
DOI: 10.3390/cryst12030339
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the Photoluminescence Intensity Caused by Ultrathin GaN Quantum Barriers in InGaN/GaN Multiple Quantum Wells

Abstract: The optical properties of InGaN/GaN violet light-emitting multiple quantum wells with different thicknesses of GaN quantum barriers are investigated experimentally. When the barrier thickness decreases from 20 to 10 nm, the photoluminescence intensity at room temperature increases, which can be attributed to the reduced polarization field in the thin-barrier sample. However, with a further reduction in the thickness to 5 nm, the sample’s luminescence intensity decreases significantly. It is found that the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It has further been shown that the luminous intensity of the samples decreases significantly as the thickness is further reduced to 5 nm. This may be caused by quantum tunneling-assisted leakage of carriers and deterioration in crystal quality, which lead to increased non-radiative losses [ 93 ]. Therefore, designing extremely thin QB samples requires fine interface quality control to meet theoretical expectations.…”
Section: Solution For Increasing Eqe Of µLedsmentioning
confidence: 99%
“…It has further been shown that the luminous intensity of the samples decreases significantly as the thickness is further reduced to 5 nm. This may be caused by quantum tunneling-assisted leakage of carriers and deterioration in crystal quality, which lead to increased non-radiative losses [ 93 ]. Therefore, designing extremely thin QB samples requires fine interface quality control to meet theoretical expectations.…”
Section: Solution For Increasing Eqe Of µLedsmentioning
confidence: 99%
“…It has further been shown that the luminous intensity of the samples decreases significantly as the thickness is further reduced to 5 nm. This may be caused by quantum tunneling-assisted leakage of carriers and the deterioration in crystal quality, which lead to increased non-radiative losses [77]. Therefore, designing extremely thin QB samples requires fine interface quality control to meet theoretical expectations.…”
Section: Mitigate the Qcse Effectmentioning
confidence: 99%
“…The observed decreased PL intensity (i.e., corresponding to the decreased radiative recombination) is essentially due to the modified charge−transfer dynamics in the system (which is depicted in Figure 6(d)). 43,44 It can be proposed that during the recombination process the excited charge carriers in TiO 2 get transferred to the CB (conduction band) of Fe 3 O 4 in the Fe 3 O 4 @TiO 2 system; however, in the cases of Ag−Fe 3 O 4 @TiO 2 nanocomposites, the electrons possibly get transferred to the CB of both Fe 3 O 4 and Ag nanoparticles, where they trap the electrons and delay their recombination possibilities. It is well known that the reduced recombination process essentially supports the improved photocatalytic reactions by extending the lifetime of the excited charge carriers by making them available in the CB of the photocatalyst for prolonged photocatalytic redox reactions.…”
Section: Morphology Analysismentioning
confidence: 99%